The Level of Knowledge and Participation of Lestari Waste Bank and Sugema Waste Bank - Annashr, Nissa Noor; Muharry, Andy; Yogaswara, Dadan; Rahim, Adzillah Himayati; Ardaya, Putri Maulidiani; Nifiyanti, Useu (Sarana Ilmu Indonesia (salnesia), 2025)
Lestari Waste Bank was founded in 2022 and started operating in January 2023, located in Tamanjaya Village, Tasikmalaya City and is not yet registered as an active waste bank. One of the waste banks that is active in Tasikmalaya City is the Sugema Waste Bank. The aim of this research was to analyze differences in the level of knowledge and participation among customers of Lestari Waste Bank and Sugema Waste Bank. This research used a cross sectional design. The population was all Lestari Waste Bank customers, totaling 44 people and all customers of Sugema Waste Bank, totaling 110 people. The sampling technique used total sampling for Lestari Waste Bank customers. Meanwhile, simple random sampling was used for Sugema Waste Bank customers, involving 95 people. The independent variable was the type of waste bank. The dependent variables were knowledge and level of customer participation. Data were collected through an interview process with a questionnaire instrument. Data analysis was carried out using univariate and bivariate analysis. Differences in mean of knowledge were analyzed using the Mann-Whitney test. Differences in customer participation levels were analyzed using the chi-square test. The results of the research showed that there was a difference in the mean knowledge of Sugema Waste Bank and Lestari Waste Bank customers (p value <0,05). There was a significant relationship between the type of waste bank and the level of customer participation (p-value <0,05). The conclusion obtained was that the knowledge and level of participation Sugema Waste Bank customers were better than Lestari Waste Bank customers.